Idiopathic Thrombocytopenic Purpura (ITP) Topic Review and Case Report - Mohamed Ahmed; Alan Y. Martinez (International Journal of Oral and Craniofacial Science - Peertechz Publications, 2017)
Idiopathic thrombocytopenic purpura (ITP) is an abnormal decrease of platelets of unknown etiologic causes. Clinical manifestations include muco-cutaneous bleeding (petechia, purpura, ecchymosis), epistaxis and/or GI bleeding. Diagnosis is made by exclusion of other causes e.g. lab error, drug or medication interaction or an infection. Prevention and control of bleeding is the most important action to do before treating the condition. This is done by transfusion of platelets. The treatment consists of steroid therapy, Anti-D immunoglobulin [1,2,3], Thrombopoietin receptor agonists or even splenectomy in some severe cases. We are presenting a case of severe ITP that was identifi ed in our dental clinic for an initial screening, our patient was admitted to the hospital and treated successfully with steroids, he presented with multiple oral and cutaneous lesions.